PENGARUH MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) BERBANTUAN MEDIA AUDIO VISUAL TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA SEKOLAH DASAR - Noer Riski Choirin Ni’mah; Ngabiyanto; Decky Avrilianda; Nuni Widiarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of applying the Cooperative Integrated Reading and Composition (CIRC) model assisted by audio-visual media on elementary school students' reading comprehension ability. This study employed a quantitative approach using a quasi-experimental desian with a nonequivalent control group design. The subjects of this study consisted of two classes, namely the experimental class and the control class, each consisting of 15 students Data were collected through tests in the form of pretest and posttest to measure students' reading comprehension ability. The results showed that there was a significant difference between the experimental class and the control class. This is indicated by the axerage posttest score of the experimental class, which was 76.00, higher than that of the control class, which was 64.67. In addition, the result of the independent sample t-test showed a significance value of 0.002 < 0.05, indicating that the application of the CIRC model assisted by audio-visual media has a significant effect on students' reading comprehension ability. Keywords: reading comprehension, CIRC, audio-visual media